Objective Assessment of Cervical Stiffness after Administration of Misoprostol for Intrauterine Contraceptive Insertion - Badir, S.; Mazza, E.; Bajka, M. (Ultrasound International Open, 2016)
The goal of this study was to objectively quantify cervical stiffness in misoprostol users prior to IUC insertion and at follow-up consultation to evaluate the feasibility of assessing cervical stiffness and to study the influence of misoprostol on cervical softening.This was a cross-sectional study that evaluated 40 women who wished to use the LNG IUS. These women were evaluated immediately before LNG IUS insertion and 6 weeks later at follow-up consultation. Participants received 200 μg of misoprostol combined with 75 mg of diclofenac in a single tablet orally (Arthrotec forte 75/200®, Pfizer, USA) 6–12 h prior to insertion in “off label” use. On both occasions, cervical stiffness was determined using a novel medical device based on the aspiration technique. The Wilcoxon rank-sum and the Wilcoxon signed-rank test were applied to compare cervical stiffness assessments at insertion of the IUD and at follow-up.For the first time, cervical stiffness was quantitatively assessed in misoprostol users prior to IUD insertion, proving that the aspiration technique enables detection of pharmacologically induced cervical changes, and also that misoprostol has a detectable softening effect on cervical tissue.The clinical value of the detected cervical softening after misoprostol administration remains unclear. Aspiration measurements could be helpful in searching for the ideal candidate, the appropriate route, dosage and interval of misoprostol intake prior to IUC insertion.
Keywords: cervical stiffness; cervical softening; cervical priming; misoprostol; aspiration technique